2006
DOI: 10.1099/vir.0.82166-0
|View full text |Cite
|
Sign up to set email alerts
|

An iterated sequence in the genome of Banana bunchy top virus is essential for efficient replication

Abstract: Banana bunchy top virus (BBTV) has a multi-component genome of circular, single-stranded DNA. BBTV replicates via a rolling-circle mechanism, probably involving sequence-specific interaction of the replication initiation protein (Rep) with iterated sequences (iterons) within the viral genome. Three putative iterons (designated F1, F2 and R), with the sequence GGGAC, have been identified in the intergenic region of each BBTV component. To investigate their role in replication, each of the iterons was mutated, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 17 publications
4
18
0
Order By: Relevance
“…The CR-SL is important for replication and contains a stem-loop structure (TATTATTAC) and an Biterated sequence^(F1, F2, and R) region (Herrera-Valencia et al 2006). The CR-M is known to be a GC-rich region, but its function is not clear (Burns et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The CR-SL is important for replication and contains a stem-loop structure (TATTATTAC) and an Biterated sequence^(F1, F2, and R) region (Herrera-Valencia et al 2006). The CR-M is known to be a GC-rich region, but its function is not clear (Burns et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Alignment of this region revealed variations at 11 positions. Three iterated sequences designated as F1, F2, and R with the sequence 'GGGAC' were found to be present in the CR-SL region of each component as shown earlier by Herrera-Valencia et al [22], and these iterated sequences are known to perform important role in the replication of BBTV. However, DNA-M contained an A in place of a G at position one of iteron F1 and iteron R is not found in DNA-U3 (Fig.…”
Section: Sequence Analysis Of the Bbtv Componentsmentioning
confidence: 87%
“…Recently Herrera-Valencia et al [15] have identified socalled ''iterated'' sequences in the genomic components of BBTV that are involved in sequence-specific interaction with the Rep encoded by the DNA-R component of BBTV. The three ''iterons'' described by them (designated F1, F2 and R), with the sequence GGGAC, are present in all the components analysed here.…”
Section: Sequence Analysis Of the Components Of Bbtv Originating Frommentioning
confidence: 99%
“…The first, known as the stem-loop common region (CR-SL), contains a predicted stem-loop structure with the loop sequence TAG/TTATTAC and repeated sequences that are likely the sequence-specific binding motifs for Rep recognition [11,15]. With similarity to the replication origins of geminiviruses (reviewed by Hanley-Bowdoin et al [16]), the CR-SL likely forms the origin of replication of BBTV.…”
Section: Introductionmentioning
confidence: 97%